$y=e^(-2x^2)$

Svolgimento:
Ricordiamo che se $f(x)=e^(g(x))=>f'(x)=g'(x)e^(g(x))$
Pertanto se $y=e^(-2x^2)=>y’=(-4x)*e^(-2x^2)$.

Commenti

commenti

Ci sono 2 commenti su questo articolo:

  1. La derivata dela funzione
    esponenziale
    y=e^(f(x),
    y’ =(1/f(x))log(e).(d/dx)f(x).
    Della funzione
    y=e^(-2x^2), y’=
    (1-2x^2).log(e).(d/dx)(-2x^2)
    =(1-2x^2).log(e)(-4x)=
    =(-4x/-2x^2).loge=(2/x)log(e).
    Nel punto
    P(xP=0,5053838263, yP=0,6)
    della funzione
    y=e^(-2x^2);
    y’P=(2/0,5053838262)log(e)=
    =-1,212921;
    -1,212921x+1,21299066=
    equazione della tangente alla funzione in P .
    y’=(-4x).e^(-2x^2) è errata.